Treatment of a Pigmented Hypertrophic Scar by Low-Level Laser Therapy (LLLT): a Case Report - Moravvaej, Hamideh; Daneshvar, Lisa; Saeedi, Mohammad; Barzegar, Mohammad Reza (Journal of Lasers in Medical Sciences, 2011)
A hypertrophic scar is defined as an excess healing response that is a dilemma for physicians. Several therapies are available: intralesional corticosteroids, topical treatments, cryotherapy, surgery, radiation, silicone gel dressing and laser therapy.Pulsed-dye, Nd-Yag and CO2 lasers have been used for treatment of keloids and hypertrophic scars but recurrence is common. Recently Low-Level Laser Therapy(aluminum-gallium-arsenide (AlGaAs) Diode 980nm, red light (Mustung, KLO4,Helium Neon 630 nm) and blue light LED lasers have been used for closure of wounds. The aim of this report is to show the effectiveness of these lasers for the treatment of a hypertrophic scar on the forearm of a 40 year-old woman due to burning by gas explosion.